2006
DOI: 10.1007/s10147-005-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcome of parosteal osteosarcoma

Abstract: POS showed characteristic findings on radiographic images. Therefore, wide resection without biopsy could be performed in 77.8% (7/9) of the cases. This procedure may contribute to attaining better limb function, because of preventing contamination of healthy surrounding tissue and minimizing the extent of resection. The safety margin was evaluated as a 1-cm-wide procedure. For the choice of reconstruction, indication of autobone grafting (3/9) or total knee replacement (TKR) (6/9) depended on tumor size, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
2
7
0
3
Order By: Relevance
“…The reason for this is that for better function less tissue needs to be removed which could result in a high risk of recurrence. We also found that the mean MSTS functional scores for the patients who had microwave-induced hyperthermia were better than scores reported in other limb salvage studies [13, 23, 24]. There could be several reasons for this, although all are somewhat speculative.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…The reason for this is that for better function less tissue needs to be removed which could result in a high risk of recurrence. We also found that the mean MSTS functional scores for the patients who had microwave-induced hyperthermia were better than scores reported in other limb salvage studies [13, 23, 24]. There could be several reasons for this, although all are somewhat speculative.…”
Section: Discussionmentioning
confidence: 40%
“…Transtibial amputation was performed as common practice [13]. The goals and requirements were resecting the bone 2 cm to 3 cm proximal to abnormal bone density, obtaining adequate length of the residual limb, and achieving good soft tissue coverage.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, since long potential medullary involvement in POS is known 19 and, in this context, has been discussed as an important issue in the decision‐making between segmental or less extensive excision 3, 7, 8. However, the incidence of local recurrence could not be linked to medullary involvement, but rather turned out as being closely dependent from adequate surgical margins 3–5, 7, 8, 15, 20. Besides, the extent of intramedullary alterations is often circumscript and still allows less extensive resection such as hemicortical excision without compromising clear margins 7, 8.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive tumor size and involvement of vessels or nerves, however, still may indicate ablative procedures. Especially, tumor effusion into the adjacent joint space makes limited excision hard or impossible to achieve and therefore mostly will require endoprosthetic reconstruction 15, 20. Throughout this retrospective study different forms of surgical treatment of POS have been applied and consequently our algorithm of indication today is based on tumor site and local extension, proximity to neurovascular structures, joint invasion, and extent of medullary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation induces tumor spread and is associated with a poor prognosis. No adjuvant therapy is necessary in low-grade lesions, but patients presenting with metastases or a high-grade POS should undergo adjuvant chemotherapy[3],[6],[10],[11],[17]–[22]. Temple et al [5].…”
Section: Discussionmentioning
confidence: 99%